Neuroimmunology of meningoencephalitis by Cryptococcus neoformans. A case report - Bárbara Padilla-Docal; Ivonne Margarita Iglesias González; Alberto Juan Dorta-Contreras (Universidad de Ciencias Médicas de La Habana, 2016)
Introduction: Meningitis/meningoencephalitis is a non-frequent central nervous system infection produced by Cryptococcus neoformans. Objective: To show the neuroimmunological response using reibergram in a patient with chronic meningoencephalitis due to Cryptococcus neoformans. Case presentation: Serum and cerebrospinal fluid IgA, IgM, IgG and albumin levels were quantified in a patient suffering from the disease by means of five lumbar punctures during her evolution; the results were plotted in their corresponding reibergram. Syntheses of at least two intrathecal major immunoglobulin were confirmed. A percent bigger of IgG intrathecal synthesis was observed. There is no blood-brain barrier dysfunction. Conclusion: Intrathecal immunoglobulin synthesis and blood-brain barrier situation constitute key element in the neuro-inflammation diagnosis. Keywords: Cryptococcus neoformans, Neuroimmunology, reibergram,   chronic meningoencephalitis.